2014
DOI: 10.1007/s10517-014-2502-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Insulin-Like Growth Factors in the Placenta in Preeclampsia

Abstract: Comparative morphological study of the placentas in women with preeclampsia and small-for-date fetuses was carried out. Expression of insulin-like growth factor-1 (IGF-1), insulin-like growth factor-2 (IGF-2), and insulin-like growth factor binding protein-3 (IGFBP-3) was detected by immunohistochemical methods. Low expression of IGF-1 and high expression of IGF-2 and IGFBP-3 in the placental tissue depending on preeclampsia severity were detected. The most pronounced changes were found in preeclampsia associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…However, studies on very premature children born small for gestational age have reported that they may be less likely to have catch-up in linear growth, or only after 6 years of age [25]. IGF-I is one of the most important regulators of postnatal growth and is known to be lower in placental tissues and cord blood in women with severe, but not mild, PE [26, 27]. Therefore, poor linear growth in children exposed to severe PE might be due to effects on the growth hormone- IGF-1 axis [2830], an effect that might be mediated through inflammation or perhaps the result of fetal programming.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on very premature children born small for gestational age have reported that they may be less likely to have catch-up in linear growth, or only after 6 years of age [25]. IGF-I is one of the most important regulators of postnatal growth and is known to be lower in placental tissues and cord blood in women with severe, but not mild, PE [26, 27]. Therefore, poor linear growth in children exposed to severe PE might be due to effects on the growth hormone- IGF-1 axis [2830], an effect that might be mediated through inflammation or perhaps the result of fetal programming.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found the insulin-like growth factor-1 (IGF-1) expression to be decreased. IGF-1 was reported to be decreased in placental tissues from women suffering PE [ 51 ]. Of note is that 38 miRNAs that putatively regulate IGF-1 ( Table 4 ) were upregulated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, circulating levels of IGF-I have been found lower in preeclamptic women [ 3 , 4 , 5 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Furthermore, low placental IGF-I expression [ 47 , 50 ] and levels [ 39 ] have been found in preeclampsia. As shown for IGF-I, maternal circulating PTHrP levels have been found lower in preeclamptic women [ 51 , 52 ].…”
Section: Calcitriol In Preeclamptic Pregnancymentioning
confidence: 99%